Optimalisasi Pengelolaan Wakaf Uang dalam Memperkuat Kemandirian Ekonomi Keluarga - Laila Nurmilah (As-Sakinah : Jurnal Hukum Keluarga Islam, 2026)
Cash waqf is an Islamic philanthropic instrument with significant potential to promote economic empowerment, particularly at the household level. In Indonesia, the potential of cash waqf is substantial; however, its utilization remains suboptimal due to low public literacy and inadequate management and distribution systems. This study aims to analyze the role of cash waqf management as an instrument for family economic empowerment and to formulate strategies for its optimization. The research employs a qualitative approach with descriptive analysis, using data collected from relevant literature, official documents, and previous studies. The findings indicate that cash waqf has strong potential as a productive financing source to enhance household economic resilience through micro-enterprise development, income generation, and improved access to Islamic financial services. However, its effectiveness depends on the implementation of professional, transparent, and accountable governance, as well as strong institutional support. One promising model is the Micro Waqf Bank (BWM), which functions as a Sharia-based financial intermediary for low-income communities. The presence of BWM expands access to financing, strengthens household business capacity, and reduces dependence on informal lending practices. Therefore, optimizing cash waqf management can serve as an effective instrument for strengthening family economic independence and improving sustainable social welfare.